Development of an in-site observation system for evaluation of dynamic deformation behavior of nucleus induced by cell substrate stretching - Naoya SAKAMOTO; Ryota UENO; Takafumi OYAGI; Naoyuki TAKESUE (Nihon Kikai Gakkai ronbunshu, 2024)
Nuclear deformation caused by external mechanical stimuli has been suggested to impact cellular activities, such as cell migration, gene expression, and proliferation; however, the underlying mechanisms remain largely unknown. Since cells reside in dynamic mechanical environments, investigation of viscoelastic behaviors of nuclei under mechanical conditions is believed to be key to understanding the mechanisms of the cellular responses to mechanical stimuli. In this study, we developed an in-situ observation system for the dynamic deformation behavior of the cell nucleus caused by mechanical substrate stretching. Human dermal fibroblasts cultured in a custom-made PDMS chamber were subjected to 5% strain by using a newly developed stretching system mounted on the stage of an inverted microscope. To obtain sequential "in-focus" fluorescent images of the nucleus during the cell stretching condition, the height of the stretching chamber was continuously controlled with a polynomial interpolation method during image acquisition. Intranuclear strains were then calculated from the fluorescence images obtained. As a result, compared to a lower strain rate condition, the whole nucleus strain in the direction of stretching tends to decrease during the application of stretching at a higher strain rate. In addition, the intranuclear strain showed heterogeneous magnitude distribution under the higher strain rate condition, while a uniform strain distribution was observed at the lower strain rate. The system we developed will help elucidate the role of the viscoelastic behavior of intranuclear structures in the cellular response to substrate stretching.